1865 Vt. Acts & Resolves 213, No. 141, § 10 - (:unkn) unknown (My University, 1865)
Authorizing Village of Rutland to appoint fire wardens to inspect the manufacture and keeping of gun powder, lime, ashes, matches, lights, fireworks, and other combustibles; authorized said fire wardens to order the persons mfring or keeping the gun powder to keep in a specified manner if they deem the manufacture or keeping unsafe.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER